Waitlist and post-transplant outcomes in patients listed with intra-aortic balloon pump for heart transplant: United Network for Organ Sharing registry. Issue 9 (September 2020) - Duran, Antonio; Nguyen, Duc T; Graviss, Edward A; Bhimaraj, Arvind; Trachtenberg, Barry; Hussain, Imad; Park, Muyng; Estep, Jerry D; Suarez, Eric E; Guha, Ashrith
Background: Intra-aortic balloon pump as bridge-to-transplant (BTT) has been used successfully in patients with refractory cardiogenic shock. However, the waitlist mortality in this population is high and predictors of waitlist mortality in this population are not known. We sought to identify predictors for waitlist mortality in patients listed with intra-aortic balloon pump and risk factors for 1-year mortality after heart transplant in this population. Methods: We identified patients listed for heart transplantation with intra-aortic balloon pump in the United Network for Organ Sharing data set from 1994 to 2015. Univariable and multivariable Cox proportional hazards models were used to identify predictors of waitlist mortality and 1-year post-transplant mortality. Results: From 1945 patients listed with intra-aortic balloon pump, 67.5% (N = 1313) were alive at 1 year and waitlist mortality was 32.5% (N = 632). We found that higher pulmonary vascular resistance, need for inotropes, and need for mechanical ventilation were associated with higher waitlist mortality. Mechanical ventilation and dialysis prior to transplantation were important predictors of 1-year post-transplant mortality. Conclusion: Predictors of mortality such as high pulmonary vascular resistance, dialysis dependence, inotrope, and ventilator dependence in patients listed with intra-aortic balloon pump can help us identify those patients that are at high risk of dying prior to a heart transplantation.